GOOD NEGOTIATOR, GREAT LEADER - MPRC, Pusat Media & Perhubungan Awam (USM, 2017)
USM, PENANG, 11 January 2017 Conflict is natural if we want to be a good leader in the future, because we humans interact with each other almost every day.